Passing patterns before and after scoring in the 2010 FIFA World Cup - Ridgewell, A. (International Journal of Performance Analysis in Sport, 2011)
The current investigation studied ball possession, passes attempted and their success rate in the 5 minutes before a goal was scored and the 5 minutes after the goal was scored when compared to a 5 minute average for the half of the match in which the goal was scored. The study analysed 121 goals from the 64 games in the 2010 FIFA World Cup. In the 5 minutes before a goal was scored, the scoring team had significantly more possession in the middle (p<0.017) and attacking thirds (p<0.001) compared to the half average. The conceding team had significantly more possession in their own defensive third before conceding than during the 5 minutes after a goal was scored (p<0.017). After a goal was scored, the scoring team had significantly lower possession in both the attacking (p<0.001) and middle thirds (p<0.017) compared to the average for the half. The conceding team significantly increased its possession in both the middle (p<0.001) and attacking thirds (p<0.017) after the goal, whilst significantly reducing possession in its own defensive third (p<0.001). In the 5 minutes before scoring, the team appears to build up pressure by increasing possession in the attacking and middle thirds.